2022
DOI: 10.3390/en15249411
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Lipases Produced by Dripping and Jet Break-Up for Biodiesel Production

Abstract: A high-performance and scalable lipase immobilization method using a dipping and jet break-up technique was reported for the production of microcapsule biocatalysts with an entrapped cascade of lipase enzyme. The lipase from Candida antarctica (CALb) recombinant Aspergillus oryzae and from the vegetal of Jatropha curcas L. (var. Sevangel) in Morelos State of Mexico were entrapped by mixing with a sodium alginate biopolymer at different concentrations. The obtained microcapsules were hardened in a CaCl2 solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Since then, the advantages of immobilized enzymes for industrial applications have been gradually demonstrated. Microcapsule is microscopic container synthesized using organic materials for the immobilization of enzymes, with particle sizes typically ranging from 1 to 1000 µm (Guzmán et al., 2022). Microcapsules have little effect on the activity of biological enzymes and can slowly release the embedded enzymes under certain conditions, which is an ideal method for enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the advantages of immobilized enzymes for industrial applications have been gradually demonstrated. Microcapsule is microscopic container synthesized using organic materials for the immobilization of enzymes, with particle sizes typically ranging from 1 to 1000 µm (Guzmán et al., 2022). Microcapsules have little effect on the activity of biological enzymes and can slowly release the embedded enzymes under certain conditions, which is an ideal method for enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%